Analysis of 7P Marketing Mix Factors on Consumer Buying Interests Dodol Kawista Cap Dewa Burung in Rembang District - Abdillah Ulfaida Rahmawanti; Sugiharti Mulya Handayani; Setyowati Setyowati (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
Kawista is a typical plant in Rembang that can be proceseds into food products, known as dodol kawista. MSME Dewa Burung is a business process which processes kawista fruit into dodol to gain higher selling value. This study aims to determine the impact of the marketing mix on consumer buying interests and to determine the variables that have the most dominant effect. The research method used is descriptive and quantitative. Sample selection using accidental sampling method with 100 respondents. The location has chosen by the purposive method. This research used primary and secondary data with observational data collection techniques, interviews, and documentation. The data were analyzed using multiple linear regression analysis using SPSS version 25. The results showed that individually variable products, places, people, processes, and physical evidence had a positive significant relationship on consumer’s buying interests, while price and promotion variables had negative significant relationship. All variables have a significant relationship collectively with consumer buying interests and the most dominant variable in process.